Stomatitis aftosa rekuren oleh karena anemia - Maharani Laillyza Apriasari; Hening Tuti (Journal of Dentomaxillofacial Science, 2010)
Recurrent aphthous stomatitis (RAS) is the common lesion in oral cavity. The etiologyof RAS remains unclear. The trigger factors are genetic, traumatic, abnormalimmunology, digestive diseases, hormonal disturbance, HIV, stress, infection andnutrition deficiency. This is a case report of a patient with minor, multiple, pain, whitecolor ulcer with erythema halo on lips palatum and tongue mucous. One day beforethe ulcers erupted, prodromal symptoms had occurred such as subfebris, malaise, anddizziness. The patient was 19-year-old, male, undergraduate student and with historyof ulceration every month. The clinical diagnosis was primary herpeticgingivostomatitis. The differential diagnosis was RAS. The complete blood count(CBC) result indicated that the patient suffered anemia. He was provided withbenzydamin HCl gargle and oral supplement contain ferrous, vitamins, and minerals.It can be concluded that anemia can be a trigger factor of RAS. Therefore, it isimportant for the dentist to know the clinical signs and manifestations of anemia inoral cavity in order to provide an appropriate treatment.